Melanoma: From Melanocyte to Genetic Alterations and Clinical Options - Corine Bertolotto (Scientifica)
Metastatic melanoma remained for decades without any effective treatment and was thus considered as a paradigm of cancer resistance. Recent progress with understanding of the molecular mechanisms underlying melanoma initiation and progression revealed that melanomas are genetically and phenotypically heterogeneous tumors. This recent progress has allowed for the development of treatment able to improve for the first time the overall disease-free survival of metastatic melanoma patients. However, clinical responses are still either too transient or limited to restricted patient subsets. The complete cure of metastatic melanoma therefore remains a challenge in the clinic. This review aims to present the recent knowledge and discoveries of the molecular mechanisms involved in melanoma pathogenesis and their exploitation into clinic that have recently facilitated bench to bedside advances.